Effectiveness of in planta control measures for Xylella fastidiosa. (15th May 2019) - ,; Bragard, Claude; Dehnen‐Schmutz, Katharina; Di Serio, Francesco; Gonthier, Paolo; Jacques, Marie‐Agnès; Jaques Miret, Josep Anton; Justesen, Annemarie Fejer; MacLeod, Alan; Magnusson, Christer Sven; Milonas, Panagiotis; Navas‐Cortés, Juan A; et al.
Abstract: This opinion updates the information included in the previous EFSA Scientific Opinion concerning the in planta control measures for Xylella fastidiosa, with a systematic review and critical analysis of the potential treatment solutions that have been published against this pest so far. The output of this opinion focuses on the application of chemical or biological treatments on living plants. In vitro studies, hot water treatments, use of resistant varieties and vector control are excluded from the review. The use of antibiotics is not considered due to the risk of antimicrobial resistance development. The use of weakly virulent or avirulent strains of X. fastidiosa is covered in this review, although this organism is an EU quarantine plant pest and its introduction in the EU territory is banned. Experiments were recently conducted to assess the effect of application of zinc, copper, and citric acid biocomplex, of N ‐acetylcysteine, and of 'diffusible signal factor' (and of its homologs). Their results showed that these control measures were sometimes able to reduce symptoms caused by X. fastidiosa . Recent experiments also showed that several species of endophytic microorganisms, some bacteriophages and inoculation of weakly virulent/avirulent strains of X. fastidiosa could offer some protection against the Pierce's disease. However, based on the reviewed results, the Panel concludes that, although several published experiments show some effects in reducing symptoms development, the tested control measures are not able to completely eliminate X. fastidiosa from diseased plants. The Panel confirms as previously stated that there is currently no control measure available to eliminate the bacteria from a diseased plant in open field conditions.